2010
DOI: 10.1098/rspb.2009.2176
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerases in apicomplexan parasites: promising targets for drug discovery

Abstract: The phylum Apicomplexa includes a large group of protozoan parasites responsible for a wide range of animal and human diseases. Destructive pathogens, such as Plasmodium falciparum and Plasmodium vivax, causative agents of human malaria, Cryptosporidium parvum, responsible of childhood diarrhoea, and Toxoplasma gondii, responsible for miscarriages and abortions in humans, are frequently associated with HIV immunosuppression in AIDS patients. The lack of effective vaccines, along with years of increasing pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 97 publications
(120 reference statements)
2
45
0
Order By: Relevance
“…1 Even in its present form, REEAD-on-a-Chip requires no specialized skills, and may be of direct use at community hospitals in non-endemic regions where lack of experience among technicians currently results in misdiagnoses and reporting delays. 2 Also, since the candidate enzyme, pTopI, is a potential new drug target in the combat against multi-drug resistant malaria 25, 26 , the presented REEAD-on-a-Chip would be an attractive setup for high-throughput drug screening. Finally, with the potential future development of REEAD substrates specific to other relevant enzyme activities the presented REEAD-on-a-Chip setup may form the basis for a more generic platform for nano-medicine or other purposes within applied or basic science.…”
Section: Resultsmentioning
confidence: 99%
“…1 Even in its present form, REEAD-on-a-Chip requires no specialized skills, and may be of direct use at community hospitals in non-endemic regions where lack of experience among technicians currently results in misdiagnoses and reporting delays. 2 Also, since the candidate enzyme, pTopI, is a potential new drug target in the combat against multi-drug resistant malaria 25, 26 , the presented REEAD-on-a-Chip would be an attractive setup for high-throughput drug screening. Finally, with the potential future development of REEAD substrates specific to other relevant enzyme activities the presented REEAD-on-a-Chip setup may form the basis for a more generic platform for nano-medicine or other purposes within applied or basic science.…”
Section: Resultsmentioning
confidence: 99%
“…This finding may open the way in exploiting the structural-dynamical properties of linkers from topoisomerase IB from different species to test their role in drug reactivity with the final aim to develop drugs selectively targeting topoisomerase IB from different species [31]. With this aim in mind we have characterized the linker domain of Top1 from the malaria causing pathogenic organism, Plasmodium falciparum .…”
Section: Introductionmentioning
confidence: 99%
“…This work suggests that T. gondii infection might contribute to certain motor, cognitive, and behavioral abnormalities[6]. Currently, additional medicines for the active infection without associated hypersensitivity and toxicity, curative medicines for the currently untreatable latent bradyzoite form of the parasite, and a vaccine to prevent infection with this parasite are being sought[711]. There have been previous studies, which indicated that peptide formulations are effective at inducing immune responses to this and other infectious agents in murine and human hosts[1216].…”
Section: Introductionmentioning
confidence: 99%